¿Intercambio O Movilidad?: Una Evaluación Sobre El Uso De Escalas De Análisis Espaciales Y Curvas De Declinación En Patagonia Centro-Meridional (Argentina). Issue 3 (September 2015) - Pallo, María Cecilia; Borrero, Luis Alberto
Abstract : Throughout south-central Patagonia, at the southern tip of South America, artifacts of black obsidian and marine materials are found at sites far from their sources. This distribution is often attributed to the existence of exchange systems among hunter- gatherer groups occupying the region in the late Holocene. In this article, we analyze distance-decay patterns in the frequencies of both items. We explore the use of decay curves for explaining the existence of exchange systems. We also discuss the notion of exchange as a means of obtaining exotic goods. We conclude that there is much intermediate variation that is not explained by the ideal extremes of exchange or mobility (i.e., direct acquisition mode). This variation includes possible visits or other types of social interaction associated with open social formations. We argue that these mechanisms are relevant to understanding the distributional patterns of goods with known source locations recorded in south-central Patagonia.